The Asian clam Corbicula fluminea (Müller, 1774) in the Guadiana River Basin (southwestern Iberian Peninsula): setting the record strait - Morais, P. (2014)
This paper aims to set the record straight regarding the first observations of Corbicula fluminea (Müller, 1775) in the Guadiana River Basin. According to the available data, C. fluminea was first observed in 1988 and not in 2006 as suggested by Pérez-Bote and Fernandéz (2008). The first observations of C. fluminea in the Guadiana estuary were reported in 2000. In 2003, C. fluminea was already well established in the estuary and in many rivers and streams. C. fluminea is likely to expand its current biogeographic distribution in Portugal, since suitable lentic habitats for colonization will be created by the implementation of the “National program of dams with high hydraulic potential”, which should be concluded by 2016.